UK, EU and global administrative law : foundations and challenges / Paul Craig. - Craig, P. P. (Paul P.) (Hamlyn lectures., 2015)
Paul Craig's analysis of UK, EU and global administrative law examines the challenges facing each system and reveals the commonalities in and differences between their foundational assumptions. The challenges which they face may be particular to that legal order, endemic to any legal system of administrative law or the result of interaction between the three systems. The inter-relationship between the three levels is important. The legal and practical reality is that developments at one level can have an impact on the other two. Legal doctrine fashioned at the national level may therefore inform developments in EU and global administrative law. The doctrine thus created may then function symbiotically, shaping developments within a domestic legal order. The inter-relationship is equally marked from the regulatory perspective, since many such provisions originate at the global or EU level.